The myth of American exceptionalism - Hodgson, Godfrey (Yale University Press, 2009)
The idea that the United States is destined to spread its unique gifts of democracy and capitalism to other countries is dangerous for Americans and for the rest of the world, warns Godfrey Hodgson in this provocative book. Hodgson, a shrewd and highly respected British commentator, argues that America is not as exceptional as it would like to think; its blindness to its own history has bred a complacent nationalism and a disastrous foreign policy that has isolated and alienated it from the global community. Tracing the development of America's high self regard from the early days of the republic to the present era, Hodgson demonstrates how its exceptionalism has been systematically exaggerated and--in recent decades--corrupted. While there have been distinct and original elements in America's history and political philosophy, notes Hodgson, these have always been more heavily influenced by European thought and experience than Americans have been willing to acknowledge. A stimulating and timely assessment of how America's belief in its exceptionalism has led it astray, this book is mandatory reading for its citizens, admirers, and detractors.